Proline catalyzed sequential alpha-aminooxylation or -amination/reductive cyclization of o-nitrohydrocinnamaldehydes: a high yield synthesis of chiral 3-substituted tetrahydroquinolines - Rawat, Varun; Kumar, B. Senthil; Sudalai, Arumugam (Organic & Biomolecular Chemistry, 2013)
A new sequential organocatalytic method for the synthesis of chiral 3-substituted (X = OH, NH2) tetrahydroquinoline derivatives (THQs) [ee up to 99%, yield up to 87%] based on alpha-aminooxylation or -amination followed by reductive cyclization of o-nitrohydrocinnamaldehydes has been described. This methodology has been efficiently demonstrated in the synthesis of two important bioactive molecules namely (-)-sumanirole (96% ee) and 1-[(S)-3-(dimethylamino)-3,4-dihydro-6,7-dimethoxy-quinolin-1(2H)-yl]- propanone (92% ee).